ESTs, cytogenetic stocks, and other tools for oat genomics - Rines, Howard W.; Phillips, Ronald L.; Anderson, Olin D.; Vance, Carroll P.; Crossman, Curt C.; Lazo, R. Gerard; Miller, Susan S.; Taller, Jennifer M. (MTT, 2004)
The development of tools for structural and functional genomics is essential for the application of these technologies to oat genetics and germplasm improvement. To supplement the fewer than six hundred DNA expressed sequence tags (ESTs) present to date in public data bases for oat, we have sequenced and are annotating for submission to GenBank an additional ~7,700 oat EST sequences. These 5' single pass sequences are derived from random clones isolated from cDNA libraries developed from polyA RNA isolated from 3-week-old green leaf (~2,500 clones), 6-day-old etiolated leaf (~2,600 clones), and 6-day-old root tissue (~2,500 clones) of 'Ogle-C', a reselection of cv. Ogle. About 85% of the oat sequences match Triticeae sequences present in the data base. We have been developing and characterizing cytogenetic stocks to use for relating previously identified oat genetic linkage groups to physical chromosome. Detection of molecular marker deficiencies in monosomic and nullisomic lines, where the missing chromosome or chromosome pair has been identified by C-banding analysis, has allowed assignment of most of the major oat linkage groups to chromosome for the monosomic stocks available. New monosomic stocks are being produced and characterized in an attempt to obtain a complete monosomic series in a single genetic background, cv. Sun II. These are recovered as products of abnormal meiosis in haploid oat plants derived from crosses of oat x maize. The described materials together with genomic tools reported from other labs including a barley DNA gene chip showing about 27% cross detection with oat expressed RNAs (Close et al. 2004), a DNA large fragment library for diploid oat (Bakht et al. 2003), and additional ESTs (e.g. Bräutigm et al., Molnar, this conference) provide opportunities for not only improved understanding of oat genome structure and function but also applications to oat genetic improvement. Close, T.J. et al. 2004. Plant Physiology 134:960-968; Bakht, S. et al. 2003. http://www.intl-pag.org/11/abstracts/P2a_P82_XI.html.
Keywords: Ka; EST; cytogenetics; monosomics; genomics